Sustainable future: A systematic review of city-region development in bay areas - Tian, Zhen; Zhou, Bowen (Frontiers in Sustainable Cities, 2023)
Despite the increasing interaction between bay area development and urban landscape transformation, the fragmented literature did not address the question: how to achieve sustainable development in the Bay Area? The objective of this study was to review the literature on four representative bay areas from both the West and the East, including the San Francisco Bay Area, New York Bay Area, Tokyo Bay Area and Guangdong–Hong Kong–Macao Greater Bay Area. This study aimed to address the following two questions: What are the ongoing research trends in the field of bay areas? What are the most critical urban issues for future Bay Area development? We used a systematic review to examine publications from the Scopus database, and bibliometric analysis was performed using the VOS viewer to visualise research results and outcomes. The results revealed that the majority of the bay area-related studies emphasised environmental issues, focused on decentralisation and policy interactions, and the field of education received limited attention. This study contributes to the comprehensive understanding of the city-region development and provides policy suggestions for future sustainable bay area development.